2020
DOI: 10.1002/adfm.202002918
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Built‐In Electric Field within Silver Phosphate Photocatalyst for Enhanced Removal of Recalcitrant Organic Pollutants

Abstract: Semiconductor photocatalysis technology has aroused great interest in photocatalytic degradation, but it suffers from the drawbacks of fast electron‐hole recombination and unsatisfactory degradation efficiency. Herein, a novel photocatalyst Ag3PO4@NC with excellent photocatalytic activity is successfully prepared, characterized, and evaluated for the efficient removal of organic pollutants. After visible light irradiation for 5, 8, and 12 min, the photocatalytic degradation efficiency of norfloxacin, diclofena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(56 citation statements)
references
References 55 publications
0
56
0
Order By: Relevance
“…30 In this regard, constructing built-in elds at the heterointerface to promote a spontaneous electron transfer process will supply more possibilities for generating desirable two opposite charged regions. 41 This design concept has been conrmed by the investigation of various perovskite-based semiconductor catalysts, which can constitute distinct p-n junctions and thus accelerate local charge redistribution at the heterointerface. 40 The band theory of solids has conrmed that the behavior of electron transfer is strongly correlated to the work function of semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…30 In this regard, constructing built-in elds at the heterointerface to promote a spontaneous electron transfer process will supply more possibilities for generating desirable two opposite charged regions. 41 This design concept has been conrmed by the investigation of various perovskite-based semiconductor catalysts, which can constitute distinct p-n junctions and thus accelerate local charge redistribution at the heterointerface. 40 The band theory of solids has conrmed that the behavior of electron transfer is strongly correlated to the work function of semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonaceous materials have been determined as functional supports with great potential owing to their advantages of low cost, easy availability, tunable physicochemical properties, and electronic structures. [9,18] The doping of nitrogen atoms with high spin and charge density into the carbon framework can give carbonaceous materials extraordinary electron-donating capability, further improving the activity of various catalysts, especially transition metal oxides. [17][18][19] For example, Li et al claimed that the electron-donating behavior of N-doped carbon materials to Fe species results in the electron-rich state of Fe atoms, thereby promoting the catalytic activity of Fe-based catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[9,18] The doping of nitrogen atoms with high spin and charge density into the carbon framework can give carbonaceous materials extraordinary electron-donating capability, further improving the activity of various catalysts, especially transition metal oxides. [17][18][19] For example, Li et al claimed that the electron-donating behavior of N-doped carbon materials to Fe species results in the electron-rich state of Fe atoms, thereby promoting the catalytic activity of Fe-based catalyst. [17] Chen et al revealed that electron-donating N-doped carbon materials can increase the dispersion of cobalt nano-particles via enhancing the metal-support interaction, leading to the improvement of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using Ag would be more eco-friendly and easier to apply in the industry. [32][33][34][35][36][37][38] The deposited Ag nanoparticles (Ag NPs) on the photocatalyst surface can effectively suppress the recombination of photogenerated electron-hole pairs due to the Schottky barrier formed at the interface between the metal and semiconductor. Moreover, surface plasmon resonance (SPR) of Ag NPs signicantly improves the absorption of visible light.…”
Section: Introductionmentioning
confidence: 99%